Utilization Of Mahogany (Swietenia Macrophylla) As An Environmental Damage Mitigation Strategy Post-Mining In Indonesia Through The ABCD Approach - Yuliani, Naning; Nur Kholish; Satria, Alfian Putra; Wijaya, Andre Surya; Anjani , Nisa; Sholichah, Siti; Apriyanti, Zustine (PUDAK: Local Wisdom Community Journal, 2024)
Indonesia is one of the countries in the world that has a variety of abundant natural resources which are used to meet daily needs, especially abundant mineral resources. With the presence of minerals, mining activities are increasingly massive and intensive. Therefore, it can cause environmental damage and disrupt human health, so little by little the environment will begin to experience damage due to mining activities. Apparently this can be overcome by carrying out tree planting activities to limit environmental damage. A tree that can be planted and thrives anywhere is mahogany whose Latin name is (Switemnia Marchpollya) which is able to survive in any soil conditions ranging from 88% to 99% with a large tree diameter. For the method, the author uses the ABCD method, which includes exploring and formulating possible strengths that can be used as potential. namely looking for past dreams that need to be used as motivation in achieving success in common goals. Dream is determining the flow of goals together with the community in achieving success, and the last one is carrying out the goals that have been set in order to succeed in achieving them. And finally, for the results and discussion, before planting the tree, first select the tabamab seeds, make a hole to plant them and carry out.